The digital transformation, funding constraints, and the green innovation of transportation companies - Xuqian, Wen (Frontiers in Environmental Science, 2024)
Facing increasingly pressing environmental issues, driving green transformation through innovation has become a necessary path for the future development of companies. Empirical analysis based on the sample of listed companies in the transportation sector in China from 2011 to 2021 reveals that digital transformation in transportation companies can promote green innovation. Furthermore, the impact of digital transformation on green innovation is sustained, with the lagged effect of digital transformation having a greater influence on green innovation than the current effect. The study also discovers the presence of a mediating effect of financing constraints between digital transformation and green innovation. Further research, using the promulgation of the Digital Transportation Development Plan Outline in 2017 as a quasi-natural experiment, employs the difference-in-differences method to verify the impact of the policy on green innovation in transportation companies before and after its implementation. The results demonstrate the introduction of digital policies contributes to promoting green innovation in companies. Economic consequences research suggests that green innovation can effectively reduce carbon emissions intensity. With the goal of the "carbon peaking and carbon neutrality" strategy, actively promoting the integration of digitalization and green innovation is crucial for enhancing the sustainable development of transportation companies.